Advancing Immunotherapy in Gastroesophageal Cancer Through Rational Combinations and Biomarkers - Cetin, Bulent; Wabl, Chiara A.; Gumusay, Ozge (Taylor & Francis Ltd, 2023)
The impact of checkpoint inhibitors on gastroesophageal cancer treatment has been tremendous in the last 2 years. KEYNOTE-590, CHECKMATE 649 and CheckMate 648 are landmark trials that have introduced immunotherapy to the field as first-line therapy, leading to a paradigm change for advanced esophageal and gastric cancer. Chemotherapy in combination with immunotherapy is now the standard of care for first-line treatment of locally advanced or metastatic adenocarcinoma of the esophagus, esophagogastric junction and stomach. Several new targets and treatments are available for gastroesophageal cancer that are based on the characterization of cancer cells and the tumor microenvironment. Biomarker-based therapy selection is critical to optimize outcomes and minimize toxicities, as well as give insight into the optimal timing and sequence of a patient's treatment course. Plain language summaryDoctors have found a better treatment for advanced esophageal and stomach cancer. They combined two types of medicines called immune checkpoint inhibitors and chemotherapy. This made more people respond to the treatment and live longer without the cancer getting worse. They use a test called PD-L1 Combined Positive Score to see if the treatment will work but, when looking at the results, there remain challenges and new treatments and tests are still needed for these cancers.
Gumusay, Ozge/0000-0002-6236-9829
Keywords: Biomarker Testing; Esophagogastric Cancer; HER2-Targeted Therapy; Immunotherapy; Novel Immunotherapies; PD-L1